Are graduated compression stockings still essential for VTE prophylaxis in general surgical patients? - Schulz, S. L.; Stechemesser, B.; Seeberger, U.; Müller, S.; Andresen, D.; Baer, U. (Phlebologie, 2008)
Background: Current guidelines for the prevention of venous thromboembolism in surgical patients continue to recommend the use of graduated compression stockings in addition to low molecular weight heparins (LMWH). Nearly all the studies documenting a prophylactic benefit from these stockings were carried out before the introduction of LMWH. Patients, methods: We studied the rate of symptomatic venous thromboembolism (VTE) occurring in patients of a general surgery department during two consecutive time periods of 24 months with different prophylaxis regimen. During the first 24 months (Group A), preventive measures consisted of LMWH and graduated compression stockings. During the second 24 months (Group B) only LMWH was used. Results: In Group A there were 3181 patient with a total of 3050 operations. In Group B there were 2986 patients with a total of 2911 operations. 82.5% of the patients in Group A and 84.0% in Group B received VTE prophylaxis (stockings and LMWH in A, LMWH only in B). Symptoms suggesting venous thromboembolism occured in 44 patients in Group A and in 47 in Group B. Examinations of these patients revealed a VTE in 7 A and 5 B patients. Conclusions: The incidence of symptomatic venous thromboembolism in patients of a general surgery department was kept low with a simple, but strictly applied preventative protocol of LMWH. Graduated compression stockings did not yield additional benefits in our patients.
Keywords: Venous thromboembolism; VTE-prophylaxis; low molecular weight heparins; graduated compression stockings; pulmonary embolism